Early post-marketing experience with edaravone in an unselected group of patients with ALS. Issue 3 (3rd April 2019) - Abraham, Alon; Nefussy, Beatrice; Fainmesser, Yaara; Ebrahimi, Yoram; Karni, Arnon; Drory, Vivian E.
Abstract: Introduction : Treatment with edaravone has shown efficacy in a subgroup of patients with amyotrophic lateral sclerosis (ALS). However, it has been estimated that <7% of ALS patients fulfill the stringent inclusion criteria of the trial. In the current study, we aimed to explore retrospectively the efficacy of edaravone in unselected ALS patients. Methods : Demographic and clinical data were retrospectively collected for 22 patients who opted for treatment with edaravone and 71 untreated ALS patients attending the ALS clinic at Tel Aviv Sourasky Medical Center, Tel Aviv, Israel, between May 2017 and January 2018. Clinical data were extracted for a baseline visit at treatment onset, and for pre-baseline and post-baseline visits, roughly 6 months apart from the baseline visit. Results : Baseline demographic and clinical characteristics were similar between edaravone treated and untreated patients, except for shorter disease duration in edaravone treated patients. Muscle strength, ALS Functional rating scale (ALSFRS-R), and respiratory function were similar between edaravone treated and untreated patients, including monthly rate of decline before and after baseline visit. Among treated patients, 7 had major respiratory complications occurring between 8 days to 7 months after treatment initiation, during or within hours following infusions. Discussion : Results of our study comparing edaravone treated and untreated patients in a real-life setting showed no differences in the rate of monthly decline of ALSFRS-R, in line with previous reports in ALS patients not treated with edaravone, and a previous clinical trial. Our findings might suggest that edaravone is not effective in unselected ALS patients.